Evaluating Antiinflammatory and Antiandrogenic Effects of Garden Cress (Lepidium sativum L.) in HaCaT cells - KARTAL, MURAT; Turkoglu, Murat; Kilic, Songul; Pekmezci, Erkin; KARTAL, MURAT (My University, 2018)
Lepidium sativum L. (Brassicaceae) (Ls), garden cress, is an edible herb that is botanically related to watercress and mustard, sharing their peppery, tangy flavor and aroma. The various parts of the plant have been traditionally used for many respiratory, rheumatologic, cardiovasculary, metabolic, and gastrointestinal disorders. Several studies were performed showing its antiinflammatory, anticarcinogenic, antiproliferative as well as tissue protective effects. In all of these studies the positive effects of Ls were concluded as the result of its antioxidant features due to the polyphenols and organosulphur compounds. In this study, we investigated the molecular basis of antiinflammatory, antiproliferative, antimitotic and antiandrogenic effects of Ls leaf extract in HaCaT cells. The gene expression levels of vascular endothelial growth factor (VEGF), tumor necrosis factoralpha (TNF-alpha), interleukin 1-alpha (IL-1 alpha), and 5 alpha-reductase type II (SRD5A2) were studied. Gene expressions were determined by RT-qPCR analysis. Fold change results of the gene expression analyses showed that the plant extract caused statistically significant downregulation of VEGF (0.2167, p< 0.0001), TNF-alpha (0.4133, p = 0.0262), and SRD5A2 (0.0567, p< 0.0001). The fold change for IL-la was 0.6900 and this result was not statistically significant (p = 0.1522). These preliminary results may partially explain the clinical success of Ls in the traditional medicine. Considering these results, topical application of Lepidium sativum extract may be beneficial for inflammatory, androgen dependent disorders of the skin.